Pengaruh Pengalaman Organisasi Himpunan Mahasiswa Jurusan Terhadap Kesiapan Kerja Bagi Fresh Graduate Universitas Nahdlatul Ulama Kalimantan Barat - Sari, Nia Puspita; Firayanti, Yuni; Marhamah, Marhamah (Lembaga Pendidikan dan Penelitian Manggala Institute, 2025)
This study aims to determine the effect of departmental student association organizational experience on work readiness for fresh graduates of Nahdlatul Ulama University of West Kalimantan. This study uses a quantitative approach with a survey method by distributing questionnaires to 33 respondents who are alumni of UNU West Kalimantan in 2024 and have been active in the Departmental Student Association organization. The research instrument was tested for validity and reliability, and all items were declared valid (r count> r table 0.344) and reliable (Cronbach's Alpha value> 0.70). The results of simple linear regression analysis show a positive and significant influence between organizational experience on work readiness with the regression equation Y = 14.205 + 0.299 + e and a significance value of 0.000 (<0.05). The coefficient of determination (R²) value of 0,557 indicates that organizational experience contributes 56% to work readiness, while the rest is influenced by other factors. Based on these results, it can be concluded that organizational experience in student associations of the department has an important role in improving graduates' work readiness.